2023
DOI: 10.3389/fimmu.2023.1208822
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of IgG antibody response against Plasmodium antigens among Nigerian infants and young children

Colleen M. Leonard,
Perpetua Uhomoibhi,
Ado Abubakar
et al.

Abstract: BackgroundPlasmodium falciparum malaria is a leading cause of child mortality in Nigeria. Neonates are born with maternal antibodies from placental transfer which may protect against malaria infection in the first months of life. The IgG dynamics of the transition from passively transferred antimalarial antibodies to actively acquired IgG from natural exposure have not been well elucidated.MethodsBlood samples collected during a 2018 Nigeria nationwide HIV/AIDS household survey were available for 9,443 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Inside the red blood cells, the parasites multiply and eventually cause the cells to rupture, releasing more merozoites to infect other red blood cells. Multiple studies have identified various invasion-related protein molecules mediating the invasion process of Plasmodium falciparum , such as Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1), Plasmodium falciparum merozoite surface protein 1 (PfMSP1), Plasmodium falciparum apical membrane antigen 1 (PfAMA1), Plasmodium falciparum rhoptry neck protein 4 (PfRON4), with PfEMP1 being particularly important ( Lee et al, 2023 ; Leonard et al, 2023 ; Pulido-Quevedo et al, 2023 ; Wiser, 2023 ). In recent years, the involvement of Plasmodium helical interspersed subtelomeric (PHIST) proteins in the invasion process has also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Inside the red blood cells, the parasites multiply and eventually cause the cells to rupture, releasing more merozoites to infect other red blood cells. Multiple studies have identified various invasion-related protein molecules mediating the invasion process of Plasmodium falciparum , such as Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1), Plasmodium falciparum merozoite surface protein 1 (PfMSP1), Plasmodium falciparum apical membrane antigen 1 (PfAMA1), Plasmodium falciparum rhoptry neck protein 4 (PfRON4), with PfEMP1 being particularly important ( Lee et al, 2023 ; Leonard et al, 2023 ; Pulido-Quevedo et al, 2023 ; Wiser, 2023 ). In recent years, the involvement of Plasmodium helical interspersed subtelomeric (PHIST) proteins in the invasion process has also been investigated.…”
Section: Introductionmentioning
confidence: 99%